491 Clinical Characteristics and Outcomes of Patients Undergoing Emergency Appendicectomy During the Pandemic Of COVID-19 Infection – A Single Centre Experience. (4th May 2021) - Aladeojebi, A; Salgaonkar, H; Murcott, D; Cheruvu, C
Abstract: Introduction: In March 2020, the World Health Organisation declared a global pandemic with the outbreak of a novel coronavirus. As the morbidity and mortality rates increased, the healthcare system was burdened with grave challenges including decisions on how to manage patients who needed emergency surgery during the pandemic. In the absence of clear guidelines and undetermined effects of peri-operative COVID-19 infection on surgical patient outcomes; our aim was to publish our surgical outcomes for emergency appendicentomies done during the pandemic. Method: Prospective data was collated from 1st of March to 5th of June 2020 (n = 132) had appendicectomies over the period stated. Patient demographics, presenting symptoms, peri-operative events, investigations, and post-operative results and complications were documented and analysed. The results were then compared with outcomes of retrospective analysis at the same centre (n = 206) carried out from 1st March to 30th June 2019. Results: The incidence of complications of appendicitis were similar without any significant differences. The negative appendix rate was significantly lesser in 2020 group, which may correlate to strict patient selection criteria for surgery. Conclusions: Under strict selection protocols to reduce transmission of COVID- 19 and best surgical practice emergency appendicectomy is safe and feasible. However these observations warrant further well-designed future studies.